Implementasi Algoritma Zhu-Takaoka pada Aplikasi Pencarian Makanan Khas di Dunia Berbasis Android - Saragih, Ardiansyah Reza (STMIK Budi Darma, 2019)
One thing that should not be missed by a traveler is tasting the typical food of the country that is being visited. However, they still don't know what special foods are in the country. You can use the Google Search service to find information on these special foods, but you need an internet connection. The problem is, maybe the country that is being visited is difficult to get an internet connection, or the traveler runs out and forgets to fill out his smartphone's internet quota, or maybe his smartphone cellular operator can't be used abroad. If you buy a new sim card that is suitable for the country you visit, of course it is troublesome. Because every time you change countries you have to buy a new sim card that suits the country you are visiting. To overcome this problem, a simple application that is operated on an Android-based smartphone that is useful helps us find special foods from various countries. This application is very simple and is offline, which means it does not require an internet connection. Users only need to enter the name of the country and what foods will appear in that country. Application designed using one of the search algorithms, namely Zhu-Takaoka. The Zhu-Takaoka algorithm is a development of the Boyer-Moore algorithm.